Cyclical cholera outbreaks in Ghana: filth, not myth - Nana Mireku-Gyimah; Paschal Awingura Apanga; John Koku Awoonor-Williams (BMC, 2018)
Abstract Background Ranked among the world's dirtiest countries, Ghana has poor environmental sanitation and hygiene, and a lack of potable water, all of which combined have been largely blamed as the underscoring reasons for cholera outbreaks. The country has concomitantly suffered seasonal cholera outbreaks that have impacted negatively on the population's health, as well as on the nation's economy. To prevent cyclical cholera outbreaks in Ghana, this commentary discusses the associated problems and makes recommendations to solve them. Main body This commentary aims to throw light on the menace of cholera in Ghana and the need to curb the recurrence of outbreaks and bouts of this epidemic. Response measures, challenges, and lessons learnt from the most recent cholera outbreak are critically assessed to determine how best this public health issue could be resolved. General and specific policy recommendations are identified in this regard. Conclusion To resolve this problem, there is a need for an oral cholera vaccine to be introduced. There is also a need to develop strategies and interventions relating to water, sanitation, and hygiene, to be initiated by the Ministry of Health, with component activities that are culturally tailored to Ghanaian communities. Policy change towards the prevention of outbreaks in Ghana is identified as another requisite.